2017
DOI: 10.1556/2006.6.2017.039
|View full text |Cite
|
Sign up to set email alerts
|

Gaming disorder: Its delineation as an important condition for diagnosis, management, and prevention

Abstract: Online gaming has greatly increased in popularity in recent years, and with this has come a multiplicity of problems due to excessive involvement in gaming. Gaming disorder, both online and offline, has been defined for the first time in the draft of 11th revision of the International Classification of Diseases (ICD-11). National surveys have shown prevalence rates of gaming disorder/addiction of 10%–15% among young people in several Asian countries and of 1%–10% in their counterparts in some Western countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
250
0
22

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 401 publications
(296 citation statements)
references
References 53 publications
4
250
0
22
Order By: Relevance
“…Article first published online: December 1, 2017 in the Journal of Health Psychology, Post-print Version https://doi.org/10.1177/1359105317740414 status of IGD as a bona fide addiction (Kuss et al, 2017ab;Saunders et al, 2017), the term PGB was adopted throughout this study.…”
Section: Article Informationmentioning
confidence: 99%
“…Article first published online: December 1, 2017 in the Journal of Health Psychology, Post-print Version https://doi.org/10.1177/1359105317740414 status of IGD as a bona fide addiction (Kuss et al, 2017ab;Saunders et al, 2017), the term PGB was adopted throughout this study.…”
Section: Article Informationmentioning
confidence: 99%
“…However, it is important to acknowledge that significant increases in gaming may not always be beneficial and may pose risks for vulnerable individuals including minors and those affected by and at risk of gaming disorder (King, Koster, & Billieux, 2019). Recognized negative impacts of excessive gaming, including harm to mental health, sleep patterns or physical health (Saunders et al, 2017), may be difficult to discern due to the imposition of work/schoolat-home practices. Protracted periods of isolation, technology-based activity, and limited face-to-face interaction have the danger of solidifying unhealthy lifestyle patterns, intensifying technology-related disorders and leading to difficulties to readaptation when the COVID-19 crisis has passed.…”
mentioning
confidence: 99%
“…More recently, gaming disorder was included in the latest revision of the International Classification of Diseases (ICD‐11; World Health Organization, ). Although the ICD and DSM systems differ in their clinical description of gaming disorder, both systems state that the disorder has similar characteristics to gambling disorder (e.g., prioritization of gaming over other activities, loss of control, and functional impairment) (Saunders et al, ). Numerous epidemiological studies (e.g., Haagsma, Pieterse, & Peters, ; Müller et al, ; Przybylski, Weinstein, & Murayama, ; Rehbein, Kliem, Baier, Mößle, & Petry, ) have reported that the prevalence of gaming disorder exceeds 1% of the general population, with much higher estimates among adolescents (Mentzoni et al, ; Müller et al, ; Mak et al, ; van Rooij, Schoenmakers, Vermulst, Van Den Eijnden, &, Van De Mheen, ; King, Delfabbro, Zwaans, & Kaptsis, ).…”
mentioning
confidence: 99%